Factores del bajo rendimiento escolar del Inicial 2 en la Escuela de Educación Básica Particular Nuevo Milenio del cantón Cuenca, 2018-2019 - Jara Avila, Alba Michelle (2020)
Academic performance is the reflection of the learning generated in a process which shows if the goals set within the school context whether or not were achieved. In this case analysis you can understand the main socio-demographic variables and the behavioral characteristics of students related to their scholar performance.